IMPLEMENTASI KEBIJAKAN BANTUAN DANA BIAYA OPERASIONAL SEKOLAH (BOS) DI KOTA PALU - Wahid, Abd. (Katalogis, 2014)
The purpose of the research is to be achieved : To determine and analyze the PolicyImplementation Assistance Fund Operating Expenses (BOS ) in Palu , the research method used is qualitative , and in this study there were some informants who understand the problems studied , as for who is the informant here is as follows: Head of Education Palu , Head of Basic Education , the School Committee , the Parent recipient BOS, Elementary School Principal and Principal of Instruction Petobo SDN 06 Lolu , type of data used is primary data and secondary data . Data was collected through observation , interviews , and documentation . The researchers of this study suggest several research results , communication is one of the main factors in policy implementation , communication becomes a major pathway for the implementation of each program. Human resources are the main factors that should be held by each institution or unit both government and non-government institutions , Vice versa if the perspectives of the different implementing the decision makers , the process of implementation of a policy becomes increasingly sulit.dan In case - such cases the executor will use discretion and sometimes subtle ways to inhibit , or will benefit each individual in the process of policy implementation.